Mentha arvensis, a medicinal and aromatic plant, has high nutritional value and several-uses: A review - Muhammad Nazim; Qurat-Ul-Ain Sadiq; Aamir Nawaz; Shazia Anjum; Muqarrab Ali; Haseeba Maryam (Buletin Agroteknologi, 2020)
Mentha arvensis or mint is a renowned medicinal and aromatic plant. It is annual plant and cultivated in the tropical and sub-tropical regions under irrigation. Its cultivation has significant importance, such as for food flavoring, medicinal applications, essential oil applications, and also using in traditional purposes. Its essential oil contains many components phenolic, aldehydes, ketones, and carbohydrates. Menthol is a fundamental component of Mentha arvensis essential oil. Menthol has also several industrial applications, especially in food, cosmetics, pharmaceuticals, and by-products. There are many types or variations of menthol found in Mentha arvensis depending on the species or cultivars as well as cultivation conditions, such as weather, irrigation, soil type, pruning, and other agronomical practices. It has interesting and valuable botany, morphology, and ecology. Its growth rate is strongly affected by the change of variables, such as pH, temperature, and nutritional values of soil. The extraction of essential oil and the post-harvest analysis are done by using traditional methods for Mentha arvensis oil production in developing countries. Research on oil extraction methods, maximizing yield per hectare, and optimum preservation are needed for the further, especially in post-harvest of mint leaves and roots.